The Predictable Irrationality of Righteous Minds, and the Work of Ethicists. (6th May 2013) - Ubel, Peter A.
Abstract: As Jonathan Haidt explains in The Righteous Mind, it is often our moral intuitions that come first, rapidly or even automatically, with ethical reasoning coming later. Haidt's book is one of many that have come out in recent years highlighting the relevance of psychology (and its close cousin, neuroscience) for understanding human morality. As a behavioral scientist, I have devoured many of these books. I am fascinated by human nature and love trying to understand why all of us behave and think the way we do. But as a physician ethicist, I often find myself reading these books with a parallel agenda: not just to understand human nature, but also to see whether this line of research has relevance for my work as an ethicist. My bottom line: Understanding moral psychology ought to be a required component of ethics training, not because the science will help us to differentiate between right and wrong, but because it will better equip us to teach ethics in a way that promotes moral behavior in our students .